Comparison of the Effectiveness of Google Form and Quizizz on Pancasila Education Learning Outcomes in Elementary School - Iswahyudi, Didik; Suciati, Suciati; Amalia, Wa Ode Syahrina Rizky; Andarwati, Lestari (Actual Insight, 2025)
This study aims to compare the effectiveness of Google Form and Quizizz as digital evaluation media in enhancing learning outcomes and student engagement in Pancasila Education. The background of this research lies in the limited variety of evaluation tools commonly used in schools, which often reduces student motivation and participation during assessments. The research employed Classroom Action Research using the Kemmis and McTaggart model, conducted in two cycles involving students of class X.G at State Senior High School 2 Malang. Each cycle comprised four stages: planning, implementation, observation, and reflection. Data were collected through learning outcome tests, student response questionnaires, and engagement observation sheets, and analyzed descriptively, both quantitatively and qualitatively. The findings indicate that Quizizz was more effective than Google Form in improving both learning outcomes and engagement. The average student score increased from 72.5 in the first cycle to 82.1 in the second cycle, while the number of students achieving mastery rose from 18 to 26. Furthermore, student engagement improved significantly, as reflected in positive responses toward Quizizz’s gamification features such as leaderboards, instant feedback, and interactive quiz formats. Despite these positive outcomes, the study is limited to one class and two research cycles; therefore, future studies with a broader scope are recommended to validate the consistency and generalizability of the findings.